PENGARUH PRENATAL YOGA TERHADAP PENGURANGAN NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III DI PUSKESMAS BELIMBING KOTA PADANG TAHUN 2024 - Amelia, Utami Riski; Sari, Fatmi Nirmala; Putri, Afrira Esa (Alifah Health Science Symposium Proceeding, 2024)
Back pain in pregnant women is a physiological condition experienced during the third trimester of pregnancy. As many as 68% of pregnant women in Indonesia experience moderate back pain, 32% experience mild back pain, and 6.5% experience severe back pain. Prenatal Yoga One way to overcome back pain in pregnant women in the third trimester. This study aims to determine the effect of Prenatal Yoga on reducing back pain in pregnant women in the third trimester at the Belimbing Health Center, Padang City in 2024. This research method uses quantitative with a Quasy Experiment design and a one group pre-test-post-test design. Data collection was carried out from February to July 2024. The study population was pregnant women in the third trimester at the Belimbing Health Center, Padang City, totaling 97 respondents. Sampling using the Random Sampling method totaling 30 respondents who experienced back pain. Data were collected using questionnaires and observation sheets. Data were analyzed using Univariate and Bivariate analysis with the Wilcoxon statistical test. The results of the study showed that the average pain intensity in pregnant women in the third trimester before Prenatal Yoga was 4.90 and after prenatal yoga decreased to 2.97. Univariate and bivariate obtained a p-value of 0.000 or <0.005, meaning that there was a significant difference before and after prenatal yoga was given on back pain in pregnant women in the third trimester. Prenatal Yoga can be concluded that it significantly reduces the average intensity of back pain in pregnant women in the third trimester at the Belimbing Health Center, Padang City in 2024. It is hoped that health workers will facilitate prenatal yoga programs routinely to overcome complaints of back pain in pregnant women.